HUBUNGAN DURASI BERMAIN GAME ONLINE DENGAN MINAT BELAJAR SISWA DI SDN 03 KEMBANG KERANG DAYA - Munir, Muhammad; Husairi, Husairi; Alwan, Muhammad (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2024)
The purpose of this study was to determine the relationship between the duration of playing online games and students' learning interest at SDN 03 Kembang Kerang Daya. The research method used in this research is a quantitative approach with a correlation type. This research was conducted at SDN 03 Kembang Kerang Daya, with a sample of class IV, V, and VI totaling 27 students. Data collection was carried out using a research instrument in the form of a questionnaire in the form of a likert scale, interviews, observation, and documentation. The results of this study indicate that there is no positive and significant relationship between online games and students' learning interest at SDN 03 Kembang Kerang Daya. Based on the results of correlation calculations, it is known that r count < r table, namely 0.355 < 0.396. In other words, Ha is rejected and Ho is accepted. The magnitude of the relationship between online games and learning interest is only 12.60%, the rest is influenced by other factors outside of research.